New data on middle and late Albian foraminifera and biostratigraphy of the northern palaeobiogeographical district of western Siberia - Podobina, Vera M. (Geologos, 2015)
The present paper discusses foraminiferal assemblages and biozones established on the basis of studies of samples from ten borehole sequences of the Khanty-Mansiysk Horizon in the Samotlor area of the northern palaeobiogeographical district of western Siberia (Russia). In this region, middle and late Albian foraminiferal assemblages were first distinguished in western Siberia. Levels from which these assemblages have been recovered, are here referred to the following foraminiferal zones, the Ammobaculites fragmentarius-Gaudryinopsis filiformis Zone (middle Albian) and the Ammotium braunsteini-Verneuilinoides borealis assanoviensis Zone (upper Albian). Zonal assemblages are dominated by representatives of the orders Ammodiscida, Textulariida and Ataxophragmiida. Species of the ataxophragmiid genera Verneuilinoides, Pseudoverneuilina and Gaudryinopsis are the most characteristic, inclusive of several key index forms. Foraminiferal tests consist of agglutinated quartz-silica, the wall microstructure being almost exclusively medium and coarse grained. In specific composition, the Albian assemblages from the Samotlor area are similar to those from Transuralia (Russia) and to the Canadian Province, which, together with West-Siberian Province, forms the Arctic palaeobiogeographical realm